Alignment of Canada's COVID-19 policy response with barriers and facilitators for coping reported by caregivers of youth with developmental delays, disorders, and disabilities - Katalifos, Anna; Elsabbagh, Mayada; Yusuf, Afiqah; Yamaguchi, Sakiko; Scorah, Julie; Wright, Nicola; Steiman, Mandy; Shih, Andy; Shikako, Keiko (Frontiers in Rehabilitation Sciences, 2024)
Introduction The UNICEF-WHO Global Report on Developmental Delays, Disorders, and Disabilities is an ongoing initiative aimed at increasing awareness, compiling data, providing guidance on strengthening health systems, and engaging country-level partners. Data from its caregiver survey assessing impacts of the COVID-19 pandemic showed that half of youths with developmental delays and disabilities (DDDs) and their caregivers struggled to cope, with a significant portion reporting a lack of supports and difficulty managing the worsening of the child's symptoms in isolation. Governments created service strategies supporting vulnerable groups. Little is known about the alignment between COVID-19 policies for persons with disabilities and their lived experiences. Contextualizing caregivers’ experiences can promote the development of tailored public supports for these families following a public health crisis. Methods Online survey data were collected from June-July 2020, leading to a convenience sample of caregivers of youth with DDDs across Canada. Respondents answered two open-ended questions regarding challenges and coping strategies during the pandemic. We conducted a thematic analysis of responses using inductive coding on NVivo software. Overarching codes derived from the dataset were contextualized using an analysis of provincial policies published during the pandemic. Parallels with these policies supported the exploration of families’ and youths’ experiences during the same period. Results Five hundred and seventy-six (N = 576) participants answered open-ended questions. Barriers to coping included family mental health issues, concerns about the youths’ regression, challenges in online schooling, limited play spaces, and managing physical health during quarantine. Environmental barriers encompassed deteriorating family finances, loss of public services, and a lack of accessible information and supports. In contrast, caregivers reported coping facilitators, such as family time, outdoor activities, and their child's resilience. Environmental facilitators included community resources, public financial supports, and access to telehealth services. Few COVID-19 policies effectively addressed caregiver-identified barriers, while some restrictions hindered access to facilitators. Conclusion Prioritizing needs of families of youths with DDDs during public health emergencies can significantly impact their experiences and mental health. Enhancing financial benefits, providing telehealth services, and creating inclusive public play spaces are priority areas as we navigate the post-pandemic landscape.